Construction of the financial stress index and determination of thresholds for macroeconomic vulnerabilities in dollarized countries - Salazar, Saúl (2021)
The global crisis caused by COVID-19 is a major problem in the globalized economy, and for developing countries, this generates greater uncertainty in different sectors of the economy. At the beginning of the health crisis, the annual GDP growth of the dollarized countries Ecuador, El Salvador and Panama was -12.4%, -19.36%, -38.4% respectively due to several factors, among them, the stoppage of economic activity due to confinement (See Chart 1). This paralysis also affected the financial system of dollarized countries through the increase in default and the decrease in yield In this context, Miglietta & Venditti (2019) indicate that the development of indices capable of evaluating the stability or instability within the financial system are useful to make a comparison of the intensity of financial stress with historical episodes and can be related to the real sector of the economy of a country in order to take economic measures in time